Efforts To Increase Interest In Paying Zakat With Knowledge And Self-Awareness - Dewi Rafiah Pakpahan; Ahmad Fadli; Martin; Maya Andiriani; Sabaruddin Chaniago (Publisher Cv. Inara, 2021)
The concentration of this research focuses on efforts to increase interest in paying zakat which is influenced by muzak knowledge and self-awareness. The National Zakat Agency of North Sumatra was chosen as the research site where 100 muzak were used as the population and the research sample with accidental sampling technique. Data collection uses a questionnaire where the measurement scale uses a Likert scale. The results of the study prove that knowledge and self-awareness have a significant influence in increasing muzakki's interest in paying zakat. Then this self-awareness has a dominant influence when compared to the knowledge possessed by muzak, especially in increasing their interest in paying zakat.